107 Nerve Transfers in Spinal Cord Injury: Analysis of Factors Influencing Motor Recovery. (April 2023) - Javeed, Saad; Dibble, Christopher; Greenberg, Jacob K.; Zhang, Justin; Khalifeh, Jawad M.; Ray, Zack
Abstract : INTRODUCTION: Nerve transfers have the potential to reanimate lost upper limb function following cervical spinal cord injury (SCI). However, the factors influencing motor recovery following nerve transfers in cervical SCI remains unknown. METHODS: A prospective cohort of cervical SCI patients 18 years of age with American Spinal Injury Association [ASIA] grade A-C underwent nerve transfers and followed-up until 48-months. Preoperative variables included age, time-delay post-SCI, neurological level-of-injury, ASIA grades, international classification of surgery of hand in tetraplegia (ICSHT) indicating preserved upper limb function, and recipient-nerve-electrodiagnosis. Univariate analyses were performed followed by multivariable proportional-odds logistic-regression of significant predictors. The primary outcome was motor recovery in medical research council (MRC) grades categorized as: poor-recovery (MRC grades 0-2); good-recovery (grade 3); and excellent-recovery (grades 4-5). The ICSHT was categorized into very-high-level (ICSHT-0; absent-function); high-level (ICSHT 1-2; intact biceps/brachioradialis); and low-level-injury (ICSHT 3-4; intact wrist-extension/pronation). RESULTS: 21 cervical SCI patients underwent 57 nerve transfers (33 upper limbs) at median of 21 (range: 6-142) months post-SCI. At final follow-up, median-gain in triceps MRC was: 3 ([IQR] 2.5-4, p = 0.011), finger-extensors: 4 (2-4, p < 0.001), and finger-flexors: 2 (1-3, p < 0.001). On univariate analysis, age, time-delay post-SCI, and ICSHT were significantly associated with motor recovery. On multivariable analysis, the low-level-injury (ICSHT 3-4) was significantly associated with superior motor outcomes as compared to higher-level injuries (Odds ratio [OR] 12.2, 95% CI, 2.34-91.4; p = 0.005). Each month delay increased 5% odds of superior motor function (OR 1.05, 95% CI, 1.01-1.11; p = 0.03). CONCLUSIONS: The preserved motor function in upper limb (ICSHT-grouping) significantly predicts motor outcomes following nerve transfers in cervical SCI. Nerve transfers in chronic SCI (12 months) results in comparable motor outcomes to earlier reinnervation.